Circulating annexin A2 as a biomarker in patients with pancreatic cancer - Karabulut, Mehmet; Afsar, Cigdem Usul; Serilmez, Murat; Karabulut, Senem (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Background: Pancreatic cancer (PC) is a highly lethal malignancy. There are only few predictive or prognostic markers for PC. This study was conducted to investigate the serum levels of annexin A2 (AnxA2) in patients with PC and its relationship with tumor progression and known prognostic parameters. Materials and Methods: Serum samples were obtained on the first admission before any treatment. Serum AnxA2 levels were determined using enzyme-linked immunosorbent assay. Age- and sex-matched healthy controls were included in the analysis. All statistical tests were carried out using two-sided test, and P <= 0.05 was considered statistically significant. Results: The median age at diagnosis was 59 years. The most common metastatic site was liver in 23 patients with metastasis (n = 19, 83\%). At the end of the observation period, thirty-two patients (97\%) were dead. Thirty-nine percent of 23 metastatic patients who received palliative chemotherapy (CTx) were CTx responsive. Median overall survival of the whole group was 41.3 +/- 8.3 weeks (95\% confidence interval = 25-58 weeks). The baseline serum AnxA2 levels were significantly higher in patients with PC than in the control group (P = 0.01). Serum AnxA2 levels were significantly higher in the patients with high erythrocyte sedimentation rate (P = 0.04). Conversely, serum AnxA2 concentration had no prognostic role on survival (P = 0.18). Conclusions: AnxA2 is identified as a novel secretory biomarker for PC, but it has no role as a prognostic or predictive marker.
Keywords: Annexin A2; diagnostic; pancreatic cancer; serum